HYPERBOLE IN TELEVISON ADVERTISEMENTS - Christina Maya Iriana Sari; Johan Kristanto (Humaniora Scientia, 2017)
Hyperbole employs a sharp-witter arrangement of words, images or meanings, meant to produce a specific effect on an audience. This paper focuses on hyperbole in television advertisement. The aims is to know the kinds of hyperbole used in television advertisement and to discuss the purposes of using hyperboles in television advertisement. This research uses descriptive method which involves the following steps: collecting, classifying, and analyzing the data.This study presents only two types of hyperbole. Referential equivalent method is used to determine the kinds of hyperboles in television advertisement. Meanwhile, pragmatic equivalent method is used to analyze the purpose of of using hyperboles in television advertisement. The first is visual hyperbole and the second is verbal hyperbole. The purposes of using hyperboles in television advertisement are to exaggerate the ideas that need stress, to add an amusing effect in the text, and to grab the attention or to attract the customer. Keywords : hyperbole, advertisement, visual, verbal